Psychological Skills of Elite and Non-Elite Volleyball Players - Hassan Mohammadzadeh; Saadi Sami (The Society of Aging and Physical Activity (SAPA), 2014)
The present paper aimed to study and compare some psychological skills of elite and non-elite volleyball players in the City of Urmia. Statistical population included all volleyball players of Urmia in the premier league and youth competitions, among of whom 60 male athletes with an average age, weight, and height of 24±1.68, 78±2.86, and 188±2.53, respectively, were selected by non-random and purposeful method and divided into two groups of elite and non-elite. In order to collect information, the questionnaire of psychological skills assessment issued by South Australian Sports Institute (SASI) was used. The results showed that elite volleyball players, compared with non-elite ones, recorded higher scores at all levels of mental skills. In overall, the present study showed that psychological skills play a more important role in reaching the peak fitness in volleyball players and they deserve to receive more attention from coaches and athletes.